THE DIGITAL SQUEEZE: LIBRARIES AT THE CROSSROADS - PUBLIC LIBRARIES EDITION - McKendrick, Joseph (Unisphere Research, 2012)
The economy may be healing, and more funds are flowing to North America’s public libraries. However, libraries continue to feel the sting of cutbacks and budget shortfalls. In addition, the historic shift to digital libraries is accelerating. These are the findings of a new study, conducted by the Library Resource Guide (LRG)—in conjunction with Unisphere Research, the market research division of Information Today, Inc. (ITI). The survey, conducted in December 2011 among libraries listed in ITI’s American Library Directory, reveals current spending patterns for public libraries—defined as libraries supported by municipalities, counties, or communities—and provides projections for budgets and spending trends for 2012. In total, 299 public library managers or librarians participated in this year's survey. In separate reports in this series, academic, government, and special libraries are also covered. Among the participants in the survey are directors, administrators, managers, department heads, and librarians from the complete range of library settings. The largest segment, 47%, are directors and administrators, and 13% are library managers. (For detailed demographic breakdowns, see Figures 40–43 at the end of this report.) Libraries covered in the survey represent a range of structures, sizes and segments. Among the libraries covered in this survey, about one-fourth, or 23%, serve populations of fewer than 10,000 constituents, and 16% serve communities between 10,000 and 25,000 people. Another 18% service between 25,000 and 50,000 constituents. Twenty-nine percent report their communities have more than 100,000 people. Close to half, 49%, are single, independent or standalone libraries, while another 12% are single facilities that are part of a larger multi-branch system. About 27% of respondents are reporting for entire library systems with multiple branches and facilities. Another 10% did not answer for this category because they were unable to report budget figures. Geographically, the largest segment, 28%, came from the Midwest, and 23% from the Southeastern United States. Another 22% represented libraries in the Western states, and 20% in the Northeast. Seven percent of respondents are in Canadian provinces, primarily Alberta and Ontario. Key findings from the survey include the following: Overall, libraries have seen gains in their total budgets. But this is not helping them keep up with the costs of staffing, operations, and equipment. As was the case last year, most libraries continue to be forced to cut expenses, including staff training, hours, and print subscriptions. Areas seeing spending increases include ebook and digital collections acquisitions. There is a growing shift to digital offerings among public libraries. Libraries increasingly are fulfilling roles as technology hubs for their communities, with high demand for technology and career development training resources. Ebooks and other digital materials are on the rise, while print is being scaled back. More libraries are turning to the cloud to support operations or provide content. The recent economic downturn may be a temporary malady, but libraries recognize the shift to digital resources as a longterm trend that is changing the nature of their mission and services. Over the past year, attention has shifted from surviving the economic storm to delivering greater customer service, richer and more targeted resources to constituencies. One respondent sums up the various challenges that public libraries expect to face in the coming years. “Customers want up-to-date materials, access to computers with Internet, wireless access, study and meeting space, pre- and early literacy training, relevant informational and cultural programs, easy access to needed information,” says the director of a community library in Pennsylvania. “Our goal is to provide as much as of these and other services as our budget allows. Staying open 65 hours per week, 340- plus days per year is a core service that we will strive to maintain.” Another respondent explains the dual challenges public libraries face: “We need to evolve to find relevance for our brickand-mortar facilities as well as our web services,” says the senior manager of a large system in North Carolina. “This, in my opinion, is less an issue of funding support, and more an issue of administration support—realizing that existing resources can and should be reallocated to meet the growing electronic expectations of our members. The old library is gone, and it’s not coming back. We need to move forward.”
THE LIBRARY RESOURCE GUIDE BENCHMARK STUDY ON 2012 LIBRARY SPENDING PLANS
PUBLIC LIBRARIES EDITION The Digital Squeeze: Libraries at the Crossroads—The Library Resource Guide Benchmark Study on 2012 Library Spending Plans was produced by Unisphere Research and sponsored by ProQuest. Unisphere Research is the market research unit of Unisphere Media, a division of Information Today, Inc., publishers of Database Trends and Applications magazine and the 5 Minute Briefing newsletters. To review abstracts of our past reports, visit www.dbta.com/research. Unisphere Media, 630 Central Avenue, Murray Hill, New Providence, NJ 07974; 908-795-3701, Email: twilson@infotoday.com, Web: www.dbta.com. Data collection and analysis performed with SurveyMethods. © Copyright 2012, Information Today, Inc. All rights reserved.
Keywords: Public Libraries; Digital Public Library; Library Finances; Library Resource Guide; Survey